2020
DOI: 10.1159/000509780
|View full text |Cite
|
Sign up to set email alerts
|

Parcellation of the Subthalamic Nucleus in Parkinson’s Disease: A Retrospective Analysis of Atlas- and Diffusion-Based Methods

Abstract: Background: Deep brain stimulation (DBS) is an established method of treatment for Parkinson's disease (PD). A stimulation sweet spot at the interface between the motor and associative clusters of the subthalamic nucleus (STN) has recently been postulated. The aim of this study was to analyze the available clustering methods for the STN and their correlation to outcome. Methods: This is a retrospective analysis of a group of 20 patients implanted with a DBS device for PD. Atlas-based and diffusion tractography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Another recent study has demonstrated benefits using connectomics to prospectively determine patient-specific striatal DBS targets for obsessive-compulsive disorder based on fMRI with a symptom provocation task (93). Furthermore, for DBS in movement disorders, several prospective targeting methods involving DTIbased connectivity measures have been proposed to refine patient-specific targets (Figure 3) (94)(95)(96). Since anatomical targeting can be challenging due to poor landmarks on imaging or unreliable microelectrode recordings, this connectomic approach may offer an alternative or supplemental method of targeting.…”
Section: Connectomicsmentioning
confidence: 99%
“…Another recent study has demonstrated benefits using connectomics to prospectively determine patient-specific striatal DBS targets for obsessive-compulsive disorder based on fMRI with a symptom provocation task (93). Furthermore, for DBS in movement disorders, several prospective targeting methods involving DTIbased connectivity measures have been proposed to refine patient-specific targets (Figure 3) (94)(95)(96). Since anatomical targeting can be challenging due to poor landmarks on imaging or unreliable microelectrode recordings, this connectomic approach may offer an alternative or supplemental method of targeting.…”
Section: Connectomicsmentioning
confidence: 99%
“…31,56 Previous studies using fluorodeoxyglucose-positron emission tomography suggested that long-range modulation of SMA metabolism underlies improvement of the motor score by both STN-DBS 57 and tcMRgFUS subthalamotomy, 58 and some evidence points to the border between the motor and associative clusters as the most effective target. 31,56,59 In this context, our more detailed segmentation could be helpful to define the best individualized target according to predominant motor features.…”
Section: Connectivity-based Segmentation Of the Stnmentioning
confidence: 99%
“…To date, few imaging-based STN atlases have explicitly parcellated the SMA-connected region, even though this cortico-STN projection is considered to play an important role in normal motor and behavioral control and in the pathophysiology of PD. 31,56 Previous studies using fluorodeoxyglucose-positron emission tomography suggested that long-range modulation of SMA metabolism underlies improvement of the motor score by both STN-DBS 57 and tcMRgFUS subthalamotomy, 58 and some evidence points to the border between the motor and associative clusters as the most effective target. 31,56,59 In this context, our more detailed segmentation could be helpful to define the best individualized target according to predominant motor features.…”
Section: Connectivity-based Segmentation Of the Stnmentioning
confidence: 99%
See 2 more Smart Citations